Thyasiroidea (Mollusca : Bivalvia) from the mud volcanoes of the Gulf of Cadiz (NE Atlantic) - Rodrigues, Clara F.
The Thyasiroidea collected from the mud volcanoes of the Gulf of Cadiz are reviewed. Of the seven species identified only one, Thyasira vulcolutre n. sp., is closely associated with a chemosynthetic setting. This species has anatomical features typical of chemosymbiotic taxa and is compared with T. sarsi ( Philippi, 1845), T. southwardae Oliver & Holmes, 2006, T. oleophila Clarke, 1989 and T. methanophila Oliver & Sellanes, 2005. The other six, Thyasira ( Parathyasira) granulosa ( Monterosato, 1874), Thyasira tortuosa ( Jeffreys, 1881), Thyasira obsoleta ( Verrill & Bush, 1898), Axinulus croulinensis ( Jeffreys, 1847), Mendicula ferruginosa ( Forbes, 1844) and Leptaxinus minutus Verrill & Bush 1898, are previously known from typical deep- water benthic settings. Of these only A. croulinensis is known to harbour chemo-symbionts although the gill anatomy of T. tortuosa suggests that it might also be chemosymbiotic. Thyasira vulcolutre is restricted to active seeps but there is no pattern in the distribution of the other species.